Empowering Primary Education: The Synergy of Virtual Supervision and Transformational Leadership in Boosting Teacher Self-Efficacy and Learning Outcomes - Farisyi, Shalman Al; Yanto, Heri; Ahmadi, Farid (JUMPA : Jurnal Manajemen Pendidikan, 2024)
This study focuses on analyzing the influence of principal leadership and virtual classroom-based supervision on learning effectiveness in elementary schools, with teachers' self-efficacy serving as a mediating variable. The main objective of this research is to examine how the combination of effective leadership and the integration of technology in supervision can enhance the quality of learning. The study employs a survey method with a causality approach, gathering data from 200 elementary school teachers in Jakarta. Data analysis was conducted using Structural Equation Modeling (SEM) facilitated by AMOS 24 software, which enables the examination of both direct and indirect relationships between the variables. The findings reveal that principal leadership and virtual classroom-based supervision significantly impact learning effectiveness, with teachers' self-efficacy reinforcing these effects. These results suggest that leveraging technology in supervision and fostering leadership development in schools are effective strategies for improving learning outcomes. The implications of this study contribute significantly to the formulation of innovative and technology-driven educational policies, which can be utilized to enhance the quality of education at the primary school level.